2015
DOI: 10.4235/jkgs.2015.19.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Practical Application of Resistance Exercise for Prevention of Sarcopenia

Abstract: Sarcopenia is a major component of age-related frailty and also a strong predictor of disability, morbidity, and mortality in the aging population. Resistance exercise could be the most effective intervention that improves muscle mass, muscle strength, and physical performance, thus preventing sarcopenia in older adults. The benefits of these exercise programs correlate with the intensity and the frequency of the exercise regimes used in the trials. Clinical trials vary in terms of population, setting, and exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Muscle strength is highly correlated with muscle mass,7 and loss of muscle mass is the starting point of frailty, and in the older population, changes in body composition can be easily linked to the risk of various geriatric syndromes 8. Muscle mass varies due to various causes and can be partially improved by appropriate exercises and sufficient nutrition 9 10. However, it is not completely understood what affects the reduction in muscle mass and how it can be managed.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle strength is highly correlated with muscle mass,7 and loss of muscle mass is the starting point of frailty, and in the older population, changes in body composition can be easily linked to the risk of various geriatric syndromes 8. Muscle mass varies due to various causes and can be partially improved by appropriate exercises and sufficient nutrition 9 10. However, it is not completely understood what affects the reduction in muscle mass and how it can be managed.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of RE on the Level of Myokines through Muscle-Brain Crosstalk RE is also a practical exercise to delay aging. In addition to enhancing muscle strength, stimulating muscle hypertrophy, and delaying aging, it also has a good effect on promoting and improving cognitive function and brain memory [76][77][78]. Studies have shown that RE can promote muscle protein synthesis, increase muscle mass in skeletal muscle, and avoid muscle atrophy by activating the mTORC1 signaling pathway [79].…”
Section: Effects Of Ae On the Level Of Myokines Throughmentioning
confidence: 99%